Electricity generation from water droplets via capillary infiltrating. (June 2018) - Li, Jia; Liu, Kang; Xue, Guobin; Ding, Tianpeng; Yang, Peihua; Chen, Qian; Shen, Yue; Li, Song; Feng, Guang; Shen, Aiguo; Xu, Ming; Zhou, Jun
Abstract: Electricity generation from the interaction between water and carbon materials is a new approach in the pursuit of high-efficiency energy conversion. Here, we report that a water droplet dropping onto a piece of porous carbon film can spontaneously generate electricity under ambient conditions. Twelve 5-μL water droplets can generate a voltage up to 5.2 V and illuminate a liquid crystal display. The voltage can be controlled by modulating the direction of the droplet infiltration, the zeta potential of the porous carbon, and the ion concentration. The results demonstrate that a hydrophilic porous carbon film with water droplets may function as a cost-effective electricity generator for harvesting energy from natural resources. Highlights: Water droplet dropping onto a piece of porous carbon film can spontaneously generate electricity under ambient conditions. Twelve 5-μL water droplets can generate a voltage up to 5.2 V and illuminate a liquid crystal display. A self-powered sensor for in situ detection of water-droplet delivery and positioning on a hydrophilic surface was also demonstrated.